BENEFITS AND ANTIOXIDANT PROPERTIES OF SESAME OIL - Oltiboeva Mavsuma G’ulom qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Nowadays, the deterioration of the ecological situation, the increase of synthetic additives in food products, and the excessive demand for medicines cause various allergic, genetic, and dangerous tumor diseases in people. In order to reduce various carcinogenic and mutagenic effects entering the body from the external environment, it is necessary to increase the number of natural food products, control the entry of artificial food additives into the body, and add natural antioxidants to our diet. We can add sesame oil to the list of products that have such a beneficial antioxidant effect